Gender differences in survival and its predictors in patients after myocardial infarction: data analysis from the RIMIS register - O. S. Afonina; S. Yu. Martsevich; A. V. Zagrebelnyy; D. P. Sichinava; O. M. Drapkina (Рациональная фармакотерапия в кардиологии)
Aim. Among patients who survived acute myocardial infarction (MI) with ST segment elevation (STEMI), to assess gender differences in clinical and anamnestic indicators, long-term survival, as well as factors affecting it. To compare the effect of recurrent MI on long-term survival in men and women.Material and methods. Data from the retro-prospective RIMIS register were used. In 2017, 214 patients with STEMI were admitted to the emergency cardiology department of the vascular center, 23 (10.8%) of them died in the hospital. After 6 years, the life status of patients discharged from the hospital was assessed (191 people, 129 men, 62 women). The response was 93.2%. The factors influencing the fatal outcome were assessed using a model of proportional Coke risks separately for men and women. The primary endpoint was the overall patient’s mortality.Results. The women who survived MI were, on average, 16.5 years older than the men who survived, and they were more likely to have concomitant diseases (diabetes mellitus, obesity). During the follow-up period, 34 men (26.4%) and 26 women (41.9%) died. Kaplan-Meyer curves demonstrated significantly worse survival in women compared to men. However, after the age adjustment was introduced, the risk of death in women was lower than in men (HR =0.981 (0.968-0.993), p=0.003). The main mortality predictors in women were hospitalization before reference MI, a history of coronary heart disease, a history of cerebral stroke, and anemia. In men, the main predictor of death was the presence of disability, the fact of recurrent MI, a history of chronic kidney disease and the presence of oncology (the latter two factors were rare, respectively, in 6.2% and 3.9% of patients).Conclusion. Women suffered MI much later than men. Therefore, higher mortality rates after MI were mainly determined by concomitant diseases. The main mortality predictor in men was recurrent MI. The age-adjusted risk of death after MI is lower in women than in men.